Service Quality Evaluation Of Higher Learning Institution Café Facility Using Kano Method - S. Akmal, M.N.H. Norilani, H.I. Sihombing,R. H. Hambali; S. A. Al Shami (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to determine the factors affecting service quality and evaluate service performance at higher learning institutions that has facilities which related to the service industry. The higher learning institution’s facility should be identified and analysed in terms of the quality of service they provided. This study intends to investigate the service quality within HLI café and to represent the relationship between service quality attributes with facility layout. Three difference cafeterias were selected as case study. For this purpose, questionnaires were distributed to the patronage in order to elicit the service quality attribute that influent their selection of café in a higher learning institution. The Analytical Network Process (ANP) was used to determine the most preferable dimension of service quality and this leads to selection of café that most visited. Subsequently, each attribute of service quality dimension of the selected cafe was evaluated using the Kano method. The results show that cleanliness and facility layout were the service quality dimensions that influent patronage selection of a café. It is necessary for the café to ensure their table are dry and clean as the most attractive attribute of service quality for a café.